Rapid Determination of Fatty Acids in Ziziphi Spinosae Semen from Different Origins by Internal Extractive Electrospray Ionization Mass Spectrometry - Peng LIU; Ning WANG; Si-yu XIE; Le-ting WANG; Zhe-hao LIANG; Run-chen LAI; Man-man QIN (Zhipu Xuebao)
Ziziphi Spinosae Semen is a traditional Chinese herbal medicine, which has attracted increasing attention for its unique medicinal value and nutritional effects, and occupies a pivotal position in Chinese traditional medicine. In the clinic, it is mainly used to sedate, modulate the immune and nervous systems. In recent years, due to the increasing demand of Ziziphi Spinosae Semen, numerous counterfeit and inferior products have emerged in the market, posing a significant threat to human health. Therefore, evaluation of the quality of Ziziphi Spinosae Semen is important for its safety and efficacy. Researches have indicated that the medicinal value of Ziziphi Spinosae Semen is attributed to its abundant fatty acid components. In this study, a method of internal extractive electrospray ionization mass spectrometry (iEESI-MS) was established for simultaneous quantification of five fatty acids, including linoleic acid, oleic acid, linolenic acid, stearic acid, and palmitic acid in Ziziphi Spinosae Semen from various origins. After the conditions were optimized, methanol was chosen as the extraction solvent, the temperature of the ion transport tube was set at 400 ℃, and the spray voltage was fixed at −5 kV. The flow rate of the extraction solvent was set to 10 μL/min. The analysis was carried out under negative ion mode with mass scanning of m/z 50-300. The results showed that the linear relationships of these fatty acids are good within the range of 0.01-50.00 mg/g, with the correlation coefficient (R²) exceeding 0.992. The limits of detection (LODs) and limits of quantification (LOQs) are 0.01-0.08 mg/g and 0.03-0.27 mg/g, respectively. The average recoveries are 93.39%-102.53%, with the relative standard deviations (RSD, n=3) of all fatty acids below 6.05%. Principal component analysis (PCA) and heat map analysis revealed that quality differences among Ziziphi Spinosae Semen sourced from Hebei, Henan, and Shaanxi correspond to variations in their fatty acid contents. This method has the advantages of no needing sample pretreatment, high sensitivity, and high throughput, which can rapidly quantify the contents of fatty acids of Ziziphi Spinosae Semen in different sources.